Enhancing Students’ Engagement Through Emotional Intelligence Based Digital Tools In Indonesian Language And Islamic Education Learning - Abdul Muhid; Achmad Fawaid; Muhammad Iqbal (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Digital learning has become central to classroom practice, yet its pedagogical value remains limited when technology is used only for content delivery, assessment, or task completion without addressing students’ emotional readiness and engagement. This study examined the effect of emotion-aware digital learning using the How We Feel app on student engagement in Indonesian Language and Islamic Education. A quantitative comparative quasi-experimental design with a pretest–posttest non-equivalent control group model involved 120 secondary students at an Islamic private school in Probolinggo, divided into Indonesian Language experimental and control groups and Islamic Education experimental and control groups. The results showed that the experimental groups achieved higher engagement gains than the control groups, with large effect sizes in both subjects. The effect was stronger in Islamic Education, indicating that emotion-aware digital learning is particularly effective when aligned with moral reflection, empathy, and value internalization. Emotional engagement improved most strongly in Islamic Education, cognitive engagement increased most in Indonesian Language, and empathy emerged as the strongest predictor of student engagement. The novelty lies in integrating an emotion-tracking digital tool into subject-based learning and comparing its effects across linguistic and religious education contexts.